Dangla-Migama and Afro-Asiatic IV: Root initial *ḅ- with C2 sonants - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper is a new contribution to revealing the Afro-Asiatic heritage in the lexical root stock of the Dangla-Migama group of Chadic languages by means of inter-branch comparison primarily using, among others, the ancient Egypto-Semitic etymological evidence.